PENGENDALIAN PENYAKIT TANAMAN PADI BERWAWASAN LINGKUNGAN MELALUI PENGELOLAAN KOMPONEN EPIDEMIK - Nuryanto, Bambang (Jurnal Penelitian dan Pengembangan Pertanian, 2018)
ABSTRAKControl of rice diseases still rely on the use of synthetic chemical pesticides are relatively expensive so that control costs increase, reaching 25% of total production costs. In addition, the use of pesticides has been proven to pollute the environment, especially if applied in an uncontrolled manner. Environmental manipulation or ecological engineering has the potential to suppress the development of plant diseases. This can be done by selectively managing the cultivated components, including the selection of resistant varieties, the use of healthy seeds, perfect soil preparation, the use of organic materials, the simultaneous cultivation at the right time, balanced fertilization and regulation of irrigation crops. In addition to effective, disease control technology based on epidemic components can also reduce production costs by 60% and reduce the yield rate of rice up to 30%. Application of environmentally friendly disease control technology has many advantages in supporting the growth of rice plants. Development of ecology-based rice disease control technology at farmer level require field supervision or through a comprehensive field school.Keywords: Rice plant, disease control, ecology, epidemic ABSTRAKPengendalian penyakit tanaman padi hingga kini masihmengandalkan penggunaan pestisida kimia sintetik yang relatifmahal sehingga biaya pengendalian meningkat, mencapai 25% daritotal biaya produksi. Selain itu, penggunaan pestisida sudah terbuktimencemari lingkungan, terutama jika diaplikasikan secara tidakterkendali. Manipulasi lingkungan atau rekayasa ekologi berpeluangmenekan perkembangan penyakit tanaman. Hal ini dapatdilakukan dengan mengelola komponen budi daya secara selektif,di antaranya pemilihan varietas tahan, penggunaan benih sehat,pengolahan tanah sempurna, penggunaan bahan organik,keserempakan tanam pada waktu yang tepat, pemupukanberimbang dan pengaturan pengairan tanaman. Selain efektif,teknologi pengendalian penyakit berdasarkan komponen epidemikini juga dapat menekan biaya produksi hingga 60% dan mengurangitingkat kehilangan hasil padi sampai 30%. Penerapan teknologipengendalian penyakit ramah lingkungan ini memiliki berbagaikelebihan dalam mendukung pertumbuhan tanaman padi.Pengembangan teknologi pengendalian penyakit tanaman padiberbasis ekologi di tingkat petani memerlukan pendampingan dilapangan atau melalui sekolah lapangan yang komprehensifKata kunci: Padi, pengendalian penyakit, ekologi, epidemik